Uji Stabilitas Fisik Dan Hedonik Sirup Herbal Kunyit Asam Stability And Hedonic Test Of Tumeric Tamarind Syrup - Indri Kusuma Dewi; Youstiana Dwi Rusita (Jurnal Kebidanan dan Kesehatan Tradisional, 2017)
Abstract: Physical Stability, Hedonic, Syrup, Tumeric Tamarind. Tumeric have a benefit as antiinflammation so can be improved in the syrup formula. This research aimed to describe the result physical stability and hedonic test of the tumeric tamarind sirup with differences temperature storing for phormula I was saving in 5°C and phormula II was saving in 35°C for 24 hours as many 14 cyclic. It was experimental research. This research was done by testing physical stability of the tumeric tamarind sirup include to organoleptic, pH, homogenity and pour time test and also hedonic test. The result research: organoleptic test were no change for two weeks with brownish yellow colour, smell test is turmeric tamarind, flavor test is sweet and tamarind and texture is solid. pH test is stable at 4, homogenity test is stable homogen and pour time test is phormula I was storing in 5C is 8,14 second and 7,84 second, phormula II was storing in 35°C is 5,04 second and 4,14 second for 24 hour as many 14 cyclic. Hedonic test was showed result for first week at temperature 5°C is 40% of respondents are very like, 40% of respondents are like and 20% of respondents are dislike, at temperature 35°C is 40% of respondents are very like and 60% of respondents are like. While for second week at temperature 5°C is 60% of respondents are very like and 40% of respondents are like, at temperature 35°C is 80% of respondents are very like and 20% of respondents are like.